PROSES PENCIPTAAN KOMPOSISI KRAAAK! OLEH GRUP EKLIPTIKLANG COLLECTIVE - Sri Hanuraga; Wahyu Thoyyib Pambayun; I Gede Yogi Sukawiadnyana; Ni Nyoman Srayamurtikanti (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2024)
The creation of musical compositions can be inspired by various motives, both internal and external. The composition titled “Kraaak!” is a work by the music group Ekliptiklang Collective, commissioned by MelatiSuryodarmo and Rebecca Kezia as curators for the Ekayana program of the Indonesia Bertutur Festival in 2024. Thiscommission required the Ekliptiklang Collective to incorporate the intangible cultural heritage of Bali, specifically theSubak Bali concept. Through the dissertation by Mawiti Infantri Yekti, titled “Role of Reservoir Operation inSustainable Water Supply to Subak Irrigation Schemes in Yeh Ho River Basin,” Ekliptiklang Collective discoveredthat Subak is an organization of water users for fields of its members to obtain water from the same source, which hasa complex structure that ensures both autonomy and, at the same time, interdependence among its members. Thisstructure was then adapted by Ekliptiklang Collective to create a long-duration composition that integrates threedifferent musical traditions and four personal reflections on water from the regions of each member of the group.